(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
This article examines the peculiarities of transferring the communicative and pragmatic attitude of newspaper headlines during the translation process. Newspaper headlines play a crucial role in conveying the essence of a news article while capturing readers’ attention. Translating these headlines requires careful consideration of the communicative and pragmatic stance embedded in them. Newspaper headlines serve as effective communication tools that aim to convey the main message succinctly and efficiently. When translating this communicative environment, the translator must understand the main purpose, target audience, cultural nuances, and intended impact of the original heading.